Analisis Pengendalian Kualitas pada Produk Batang Rokok Sigaret Kretek Mesin (SKM) Menggunakan Metode Six Sigma dengan Pendekatan DMAIC di PT. XYZ - Muksin, Muhammad Ali; Asy’ari, Subchan (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to determine the causes of defects in Kretek cigarettes at PT. XYZ, and how to minimize defects in Kretek cigarettes using the DMAIC approach at PT. XYZ. Data analysis was performed using the six sigma concept, which includes DMAIC. The research results are (1) the causes of defects or defects consist of 4 factors: humans, methods, materials, and the environment. The human factor is that operators leave the machine during production fatigue and lack concentration. The method factor is not checking raw materials and the lack of instructions. Material factors include raw materials or materials of poor quality with the category of non-sticky glue and dislodged filters, and for environmental factors, there is engine noise and ambient temperature. (2) The results of the analysis of the DPMO Sigma Quality Level and Process Capability values for cigarette stick products with an attribute defect in the form of non-sticky glue produce an average DPMO value of 550716.8432 with a sigma level of 1.38. In contrast, the attribute defect in the form of Dislodged Filters produces an average DPMO value of 234511.2977 with a sigma level of 2.23. These results are categorized as low process capability, so their performance needs to be improved. Thus, recommendations for appropriate corrective actions are given, namely by providing training and training to workers. They offer directions in strengthening SOPs for checking raw materials, improving the quality standards of raw materials received, and equipping workers with equipment such as masks and ear plugs as well as higher concentrations during the production process so that defects can be minimized.